Understanding consumer choice on single-use plastic consumption in Metro Manila, Philippines - Ong, Marcelane Z. (Animo Repository, 2023)
For decades, the proliferation of single-use plastic waste has emerged as a pressing global environmental concern, with Metro Manila being no exception. This study aims to shed light on the effects of these factors on consumer behavior to have a better understanding from the lens of consumers in Metro Manila. The study employed a quantitative approach to examine the relationship between environmental awareness, consumer intention, and consumer behavior. The researchers surveyed 402 Filipino adult consumers across Metro Manila using purposive and convenience sampling techniques. Descriptive, bivariate, and regression analyses were used to draw inferences from the cross-sectional data. Results show that environmental awareness significantly affects plastic avoidance, along with consumer intention, except for consumer preferences. In addition, environmental awareness significantly affects consumer engagement along with consumer intention, except for consumer ability. Finally, environmental awareness significantly affects consumer motivation, along with consumer intention, except for consumer preferences. Understanding consumers' perspectives on product sustainability is crucial to formulating effective strategies for reducing plastic misuse. It has been discovered that raising consumer awareness about the environmental impacts of single-use plastic consumption could contribute to a shift toward sustainable practices. As the world navigates toward a more sustainable future, individuals and businesses must recognize the significance of striking a harmonious balance between economic growth, environmental preservation, and social well-being to ensure a prosperous and resilient society.